The Tragedy of Almightiness : Revaluing Ethical Life. - Schaap, Sybe (Wipf and Stock Publishers, 2016)
The Tragedy of Almightiness encircles the theme of human yearning for omnipotence, as expressed in religion and various ideologies. The central question revolves around the matter of what--in pursuing such an extreme power of the will--man seeks to achieve. While exploring the question, a thought-provoking link is made between religion and atheism; between the Biblical longing for God's promise and the Marxist appeal for man to realize that same promise. Omnipotence must vouch for the fulfilling of the promise, for justice and for man's dream of redemption. However that is not where it ends. Th.